Edukasi Perkawinan Berbasis Literasi Hukum Islam untuk Menguatkan Kesadaran Hukum Calon Pengantin - Afrizal Afrizal (Ameena Journal, 2026)
Limited understanding among prospective brides and grooms regarding marital rights, obligations, responsibilities, and legal consequences may affect their readiness to establish family life. Existing marriage education tends to emphasize general knowledge and the fulfillment of formal requirements, while Islamic legal literacy has not been adequately positioned as a central element in developing legal awareness. This study aims to analyze the concept of marriage education based on Islamic legal literacy and its contribution to strengthening the legal awareness of prospective married couples. The study employed a qualitative approach using library research. Data were obtained from books, journal articles, previous studies, laws and regulations, and other documents related to marriage education, Islamic marriage law, and legal awareness. The data were collected through documentation and analyzed using descriptive and interpretative content analysis. The findings indicate that marriage education has not fully integrated legal knowledge, understanding of legal objectives, the development of law-abiding attitudes, and the ability to apply Islamic legal principles in family life. Contextual, interactive, systematic, and continuous education has greater potential to improve prospective couples’ understanding of marital rights, obligations, conflict resolution, and the protection of each spouse’s rights. The study concludes that Islamic legal literacy should serve as a foundation for developing the materials and methods of marriage education. This study contributes to the field by proposing a conceptual framework that integrates legal knowledge, understanding, attitudes, and behavior to support the formation of legally aware, equitable, responsible, and harmonious families.